The Social Integration of Under-Privileged People in the Old Testament - BOJOR, Vasile (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Social integration was and continues to be a vital need of all historical periods. Even from the Mosaic Period, God was extremely preoccupied with the way Jewish people would integrate socially under-privileged people (orphans, widows, poor people and strangers). Moreover, the Old Testament Law stipulated for a social integration of Levites and Priests. The current article aims to give an in-depth analysis of the way how all these under-privileged social categories ought to have been regarded and treated. In addition, within the same article it has been highlighted that there was a legal demand both in Antiquity (through the code of Hamurabi) and Semitic World to integrate the under-privileged people, this issue was often the responsibility of the acting king.